Cost utility analysis of reduced intensity hematopoietic stem cell transplantation in adolescence and young adult with severe thalassemia compared to hypertransfusion and iron chelation program - Sruamsiri, Rosarin (BioMed Central, 2013)
BACKGROUND: Hematopoieticic stem cell transplantation is the only therapeutic option that can cure thalassemia disease. Reduced intensity hematopoietic stem cell transplantation (RI-HSCT) has demonstrated a high cure rate with minimal complications compared to other options. Because RI-HSCT is very costly, economic justification for its value is needed. This study aimed to estimate the cost-utility of RI-HSCT compared with blood transfusions combined with iron chelating therapy (BT-ICT) for adolescent and young adult with severe thalassemia in Thailand. METHODS: A Markov model was used to estimate the relevant costs and health outcomes over the patients’ lifetimes using a societal perspective. All future costs and outcomes were discounted at a rate of 3% per annum. The efficacy of RI-HSCT was based a clinical trial including a total of 18 thalassemia patients. Utility values were derived directly from all patients using EQ-5D and SF-6D. Primary outcomes of interest were lifetime costs, quality adjusted life-years (QALYs) gained, and the incremental cost-effectiveness ratio (ICER) in US ($) per QALY gained. One-way and probabilistic sensitivity analyses (PSA) were conducted to investigate the effect of parameter uncertainty. RESULTS: In base case analysis, the RI-HSCT group had a better clinical outcomes and higher lifetime costs. The incremental cost per QALY gained was US $ 3,236 per QALY. The acceptability curve showed that the probability of RI-HSCT being cost-effective was 71% at the willingness to pay of 1 time of Thai Gross domestic product per capita (GDP per capita), approximately US $ 4,210 per QALY gained. The most sensitive parameter was utility of severe thalassemia patients without cardiac complication patients. CONCLUSION: At a societal willingness to pay of 1 GDP per capita, RI-HSCT was a cost-effective treatment for adolescent and young adult with severe thalassemia in Thailand compared to BT-ICT.